1989
DOI: 10.1111/j.1469-7998.1989.tb02586.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization of a riparian population of the carnivorous marsupial Dasyurus geoffroii

Abstract: Radiotracking and live‐trapping were used to describe spacing patterns of Dasyurus geoffroii along the Murray River in Western Australia. Both sexes are essentially solitary, and occupy numerous dens which define stable core areas. Female core areas typically showed little or no mutual overlap, suggesting that females are intrasexually territorial. As an exception to this, a non‐dispersing daughter may share her mother's core area and successfully rear young there. Transient females were rarely encountered, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…Soderquist (1995) found greater female phascogale overlap when females were related and Oakwood (1997Oakwood ( , 2002 found that female northern quolls had exclusive core areas with some overlap in foraging areas. Scent marking has also been recorded in western quolls, northern quolls and brush-tailed phascogales, and it is believed to assist in territory marking and communication of reproductive status (Serena & Soderquist, 1989;Soderquist, 1995;Oakwood, 1997Oakwood, , 2002.…”
Section: Female Spatial Organizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Soderquist (1995) found greater female phascogale overlap when females were related and Oakwood (1997Oakwood ( , 2002 found that female northern quolls had exclusive core areas with some overlap in foraging areas. Scent marking has also been recorded in western quolls, northern quolls and brush-tailed phascogales, and it is believed to assist in territory marking and communication of reproductive status (Serena & Soderquist, 1989;Soderquist, 1995;Oakwood, 1997Oakwood, , 2002.…”
Section: Female Spatial Organizationmentioning
confidence: 99%
“…Tasmanian devils and eastern quolls of both sexes were found to be non-territorial, with extensively overlapping home ranges (Guiler, 1970;Godsell, 1983). Female western quolls, northern quolls and brush-tailed phascogales displayed intrasexual territoriality, while males occupied larger home ranges that overlapped extensively both with other males and with females (Serena & Soderquist, 1989;Soderquist, 1995;Oakwood, 1997Oakwood, , 2002.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since European settlement the distribution of the chuditch has contracted dramatically to the south-west of Western Australia (Morton et al 1989) and it is now classified as "near threatened" (IUCN 2008). Chuditch are nocturnal and den in hollow logs or burrows during the day (Serena and Soderquist 1989).…”
Section: Introductionmentioning
confidence: 99%